Towards a More Illiberal Pluralism? Reexamination of the Nahdlatul Ulama’s Turn Against Islamic Fundamentalist Groups in Contemporary Indonesia - M. Khusna Amal; Uun Yusufa; Muhammad Faiz, (Journal of Islam in Asia (E-ISSN 2289-8077), 2024)
The rise of Nahdlatul Ulama’s intolerant response to Islamic fundamentalist groups has revived the long-standing scholarly debate on the future of Indonesian pluralism in post-reform era. Some scholars have overlooked that NU's response is contrary to the principles of liberal pluralism because it violates religious freedom for minority groups. Some others argue that such response actually confirm the consistency of NU's stance as a moderate Islamic organization in protecting and advocating religious pluralism in Indonesia. However, only a few scholars have studied how intolerant responses within NU and its various forms are discussed from a more critical, emphatic and comprehensive perspective. This article examines the conflicting response within NU over Islamic fundamentalist movements. This article is a qualitative research that employs a pluralism perspective as its main approach to analyzing the data. Based on a case study of local NU in Jember (East Java), it was found that many elements of NU Jember used a repressive approach in countering Islamic fundamentalist movements. This was due to the disbandment of the FPI, the termination of religious gatherings of the HTI by the State, and the rejection of the establishment of Imam Syafi'i Islamic Junior High School by the Salafis. Some, however, used non-repressive strategy against puritanical preaching of HTI, FPI and Salafi groups that are often considered heretical and in conflict with the belief of other religious groups. As result, the NU’s attempt to protect the religious freedom from fundamentalist attack turned into a threat to principles of pluralism. Indonesia’s religious freedom, I argue, is now in slow but perceptible process of deconsolidation.